LEINER’S DISEASE - Marlintan Sukma Ambarwati; Hendra Tarigan Sibero (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Leiner’s disease is a disease affecting infants (4-20 weeks) which is a complication from seborrhoeic dermatitis, universal erythema and squama (erythroderma), usually found with anemia, diarrhea and vomit. It is followed by secondary bacterial infection. The etiology of this disease has not been known yet and also so rare. A Baby, 5 months old, had chief complain of red spots and rough shells all over the body during a week, accompanied by fever, vomit, and diarrhea. From physical findings, the general condition seemed to be in a serious illness, consciousness was compos mentis, regular pulse 96 x/minute, respiration rate 24 x/minute, temperature 37,3 OC. Nutrient status was normal (Z - Score WHO 2006 Curve). From dermatologic findings, the lesion was general, diffuse erythematous covered by rough scaly layer of squama, yellowish white, oily, wax drop phenomenon test (-). Laboratory assessment found leukocytes 16.700/ul, hemoglobin 11,1 gr/dl, hematocrit 34,4% and platelets 717.000/ul. The patient was diagnosed with Leiner’s disease and given systemic therapy dexamethasone, chlorpheniraminemaleat, paracetamol, lacto-bio, and zinc, and topical therapy gentamicyn ointment and emollients lanolin 10%. The etiology of Leiner, although has not been known yet, commonly caused by spreading seborrhoeic dermatitis. The diagnosis determined based on anamnesis, physical examination, and laboratory examination. With adequate management, clinical improvement obtained.[J Agromed Unila 2014; 1(1):28-34] Keywords: leiner’s disease, seborrhoeic dermatitis